2014
DOI: 10.1166/jnn.2014.8579
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Boron Nitride Nanotubes in Aqueous Solution by Simple Aromatic Molecules

Abstract: We report that the simple aromatic molecules successfully disentangle and disperse multi-walled boron nitride nanotubes (BNNTs) in aqueous solutions through pi-pi stacking interactions. Aromatic molecules such as derivatives of naphthalene, anthracene, and pyrene were used as dispersants and components for construction of nanohybrids. Spectroscopic analyses of water-dispersed BNNTs revealed that not only numbers of aromatic rings but also substituted functional groups were essential for dispersion capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, only positively charged agents (e.g., poly-L-lysine and poly-ethyleneimine), organic amines, or chemical species able to make π-stacking and hydrophobic interactions showed good results [73]. Synthetic structures with aromatic rings (2-naphthalenecarboxylic acid, 9-anthrancecarboxylic acid, 1-pyrenecarboxylic acid, 1-aminopyrene, and 1-hydroxypyrene) [74] and polymers containing aromatic subunits, polyaniline, Noncovalent reactions are the most frequently used approach for the surface functionalization of BNNTs [73]. However, only positively charged agents (e.g., poly-L-lysine and poly-ethyleneimine), organic amines, or chemical species able to make π-stacking and hydrophobic interactions showed good results [73].…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only positively charged agents (e.g., poly-L-lysine and poly-ethyleneimine), organic amines, or chemical species able to make π-stacking and hydrophobic interactions showed good results [73]. Synthetic structures with aromatic rings (2-naphthalenecarboxylic acid, 9-anthrancecarboxylic acid, 1-pyrenecarboxylic acid, 1-aminopyrene, and 1-hydroxypyrene) [74] and polymers containing aromatic subunits, polyaniline, Noncovalent reactions are the most frequently used approach for the surface functionalization of BNNTs [73]. However, only positively charged agents (e.g., poly-L-lysine and poly-ethyleneimine), organic amines, or chemical species able to make π-stacking and hydrophobic interactions showed good results [73].…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
“…However, only positively charged agents (e.g., poly-L-lysine and poly-ethyleneimine), organic amines, or chemical species able to make π-stacking and hydrophobic interactions showed good results [73]. Synthetic structures with aromatic rings (2-naphthalenecarboxylic acid, 9-anthrancecarboxylic acid, 1-pyrenecarboxylic acid, 1-aminopyrene, and 1-hydroxypyrene) [74] and polymers containing aromatic subunits, polyaniline, poly(p-phenyleneethynylene), polythiophene, poly(xylydienetetrahydrothiophene) and poly(sodium styrene sulfonate) [73,75] interacted with the sidewall of BNNTs via π-π stacking and created stable dispersions. It was shown that poly(p-phenylene) derivatives have the most interesting potential to disperse BNNTs among studied polymers [75].…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
“…Researchers have attempted to overcome this barrier in a variety of ways, including covalent/non-covalent functionalization, [13][14][15][16][17][18] polymer or peptide wrapping, [19][20][21][22][23][24] co-solvent systems, 25 surfactants, [26][27][28] strong acids, 12,29 and other aromatic and biomolecules. 9,10,[30][31][32][33][34] One promising way to disperse BNNTs into aqueous solution is through the use of surfactants. Surfactants are amphiphilic compounds that, when used at high enough concentrations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the aromatic groups present in Bis-GMA may have increased the interaction between the polymeric matrix and the fillers. This is because BNNTs’ sidewalls display an affinity to chemical compounds with aromatic groups due to the π-stacking mechanism or hydrophobic interactions 19,20 . For this reason, BNNTs were mixed with Bis-GMA prior to the addition of TEGDMA during the preparation of the experimental RBS tested in this study.…”
Section: Discussionmentioning
confidence: 99%